2013
DOI: 10.5489/cuaj.936
|View full text |Cite
|
Sign up to set email alerts
|

Use of a novel parenchymal clamp for laparoscopic and open partial nephrectomy

Abstract: Increasing data advocates the wider use of partial nephrectomy for renal tumours amenable to this approach. We describe the initial North American use of a novel parenchymal clamp in an open and a laparoscopic partial nephrectomy. Initial results in 3 patients (2 open, 1 laparoscopic) demonstrate excellent preservation of renal function and good oncologic outcomes. Hilar dissection was avoided in all cases and the estimated blood loss was low. In our small series, we found this device to be a safe and useful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…4,5 In patients with ideal tumor locations-in particular, polar lesions or small exophytic masses on the lateral convexity of the kidney-selective parenchymal clamping has been used to create hemostasis while avoiding systemic warm ischemia. [6][7][8][9][10] Animal studies suggest that renal function and intraoperative oxygenation profiles are improved during selective parenchymal clamping compared with complete hilar clamping, although diminished oxygenation levels are noted in the unclamped areas of the parenchyma as well. 17 We previously described our technique using a novel laparoscopic parenchymal clamp in combination with RALPN.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4,5 In patients with ideal tumor locations-in particular, polar lesions or small exophytic masses on the lateral convexity of the kidney-selective parenchymal clamping has been used to create hemostasis while avoiding systemic warm ischemia. [6][7][8][9][10] Animal studies suggest that renal function and intraoperative oxygenation profiles are improved during selective parenchymal clamping compared with complete hilar clamping, although diminished oxygenation levels are noted in the unclamped areas of the parenchyma as well. 17 We previously described our technique using a novel laparoscopic parenchymal clamp in combination with RALPN.…”
Section: Discussionmentioning
confidence: 95%
“…[6][7][8][9] With an open jaw diameter of 70 mm, the Simon clamp is novel in that it has a standard ratchet handle that can be locked into place, thereby preventing clamp sliding while curved jaws evenly distribute a constant and uniform pressure. 10 An additional benefit of the laparoscopic clamp is that it allows for immediate pathologic review of tumor/margin status without concern for warm ischemia as well as better visualization of all bleeding vessels through transient reduction in clamp compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean operative time was 238 minutes and mean blood loss was 250 mL with no transfusions or other complications. Other authors have reported similar feasibility with a laparoscopic Nussbaum clamp (Aesculap AG, Tuttlingen, Germany ®) [43] and their own proprietary circumferential clamp [44].…”
Section: Parenchymal Compressionmentioning
confidence: 87%